The Use of Transformer-Based Models for Automatic Short-answer Scoring in Education: A Systematic Literature Review - Putra, Widhy Hayuhardhika Nugraha; Md Fudzee, Mohd Farhan; Hanggara, Buce Trias; Purnomo, Welly; Pradana, Fajar; Herlambang, Admaja Dwi (Journal of Soft Computing and Data Mining, 2025)
This review focuses on recent advancements in the Automatic Short-Answer Scoring (ASAS) system in education. The primary objective of this review is to identify current trends in utilizing transformer-based models for the ASAS system. This review also aims to discuss future directions for ASAS technology. ASAS’s conventional machine learning methods were inconsistent because they rely on statistical similarity and are prone to bias. Meanwhile, transformer-based models were typically used for feature extraction, embedding, and score calculation via classification or regression. They generally served as a similarity calculator comparing students’ answers to the reference answer. We applied the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework to explore ASAS’s state of the art and uncover its future trends. Our findings reveal that transformer-based models significantly outperform traditional machine learning approaches by capturing complex context. On the other hand, LLMs excel at providing feedback and score justification. Recent studies have shown a shift toward using transformer-based models for ASAS’s complex tasks, including data augmentation and feedback generation. However, further research is needed to use LLMs and GPTs to generate explainable, fairer scores and to address data scarcity through reasoning and augmentation.